Analisis Isi Buku Naḥwu Wāḍiḥ untuk Madrasah Tsanawiyah Telaah Berdasarkan Prinsip Kemendiknas dan Ahmad Rusydi Thu’aimah - Asbarin, Asbarin; Warahmah, Mawadda; Jannah, Nidaul (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study aims to analyze the content of the book Nahwu Waḍih Volume 1 by Ali al-Jarimi and Musthafa Amin published by Maktabah al-Lughawiyah, Beirut-Lebanon, based on the standards of the Ministry of National Education in 2006 and 2008 as well as the principles of learning Arabic according to Ahmad Rusydi Thu'aimah. The research method used is a literature study with a qualitative approach, using descriptive content analysis techniques. For data analysis techniques, this study applies the Krippendorff content analysis method. The results of the study show that in general, the Nahwu Waḍih book has fulfilled the principles of preparing teaching materials according to the standards of the Ministry of National Education, such as the principles of consistency, relevance, and adequacy. However, there are some inconsistencies in the book regarding the principle of gradation. In the first chapter, this book directly discusses the jumlat al-mufīdah (perfect sentence) before explaining the basic parts of a sentence, such as the meaning and characteristics of isim, fi'il, and letters, as well as how students know how to distinguish them. This is contrary to the principle of gradation which prioritizes the arrangement of material from easy to difficult, from simple to complex, or from concrete to abstract. Meanwhile, in the Thu'aimah standard, namely the principles of validity, meaningfulness, feasibility, and global. In general, it has not been completed, because, in the principle of meaningfulness and material globalization, there is still a need for improvement. Therefore, this study recommends improvements in the aspects of gradation, meaningfulness, and globalization to be more in line with the principles of the preparation of ideal teaching materials, so that it is more useful in making Arabic teaching materials in the future.